PREDIKTIVNA VRIJEDNOST NEKIH TESTOVA MOTORIČKIH SPOSOBNOSTI ZA PREDVIĐANJE USPJEHA U BRZINI PRELASKA PREKO KONOPCA - Edin Mujanović; Ferhat Nožinović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
Main goal of this research is to analyze predictive value of motor abilities on success in overcome the obstacle over the rope. Research has been conducted on sample of 33 students the 3rd year of Faculty of physical education and sport at University of Tuzla. Predictive variables in this research are 9 motor tests and criteria variable is results of success in overcome the obstacle over the rope. Results of regressive analyze have shown that prediction of results about the success in overcome the obstacle over the rope is high and possible with variables that measuring strength and frequncy of movement. Key words: motorical abilities, students, regressive analysis, outdoors activities